2021
DOI: 10.1021/acs.jpcc.0c11529
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Pseudocapacitive Behavior, Cyclic Performance, and Field Emission Characteristics of Reduced Graphene Oxide Reinforced NiGa2O4 Nanostructured Electrode: A First Principles Calculation to Correlate with Experimental Observation

Abstract: The rational construction and design of supercapacitors (SCs) with electrochemically favorable structural configuration and appreciable cyclic performances are highly demanding. Herein, a novel Ga-based transition metal oxide, NiGa 2 O 4 , was synthesized via sol−gel self-ignition techniques to design an advanced electrode for supercapacitor and field emitter applications. Reitveld refinement of XRD, FTIR, and Raman spectra reveals a larger cubic parameter due to the incorporation of Ga over NiO, which promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 79 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…The work function can be defined as the difference of energy of an electron between the vacuum level and the Fermi level. Mathematically, the work function (φ w ) can be expressed as , Here, φ 0 , e , and E F represent the electrostatic potential of the vacuum level, charge of an electron, and Fermi energy, respectively. We found that the work function of the Q-carbon electron field emitter is around 3.62 eV, which is in good agreement with the previous experimental outcomes .…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The work function can be defined as the difference of energy of an electron between the vacuum level and the Fermi level. Mathematically, the work function (φ w ) can be expressed as , Here, φ 0 , e , and E F represent the electrostatic potential of the vacuum level, charge of an electron, and Fermi energy, respectively. We found that the work function of the Q-carbon electron field emitter is around 3.62 eV, which is in good agreement with the previous experimental outcomes .…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…We computed theoretically the quantum capacitance for the (À111) surface of MnWO 4 . Using the density of states, the quantum capacitance could be determined from the following relation: 35,64…”
Section: Theoretical Computationsmentioning
confidence: 99%
“…where D(E) denotes the density of states, whereas F G indicates the electrode potential. The thermal broadening function can be written as: 35,64…”
Section: Theoretical Computationsmentioning
confidence: 99%
See 2 more Smart Citations